Diagenesis in Modern, Danish, Burned Pig Bone - Anne Juul Jensen (EXARC, 2016)
During archaeological excavations, burned bones are often found as a result of cremation, cooking or accidental fire. Even though the bones are burned, their elemental composition might still hold information about diet, habitat and health history in the past. One problem, however, is diagenesis; a range of processes changing the structure and composition of the burned bones after burial. In order to study the effects of diagenesis in burned bones, a modern domestic pig was burned and buried. Samples of the bones and the surrounding soil were taken after nine months, and again after 21 years of deposition. The samples were analyzed elemental for Al, Mn, Fe, Pb, Ca, Sr and Ba using ICP-MS, and for Hg using CV-AAS. The results indicate that Al, Mn, Fe and Ba are affected by diagenesis, whereas Pb, Hg, Sr and Ca are not.